MOC-31 Antibody Immunolabeling During Mohs Surgery. Issue 6 (5th June 2022) - Bae, Edward; Saap, Liliana; Breen, Catherine; Iwamoto, Satori
Abstract : BACKGROUND: Ber-EP4 is an antibody that labels basal cell carcinoma (BCC) by targeting epithelial cell adhesion molecule (Ep-CAM). MOC-31, a monoclonal mouse antibody, also targets Ep-CAM and is currently used to differentiate several extracutaneous epithelial tumors. However, the utility of MOC-31 has not been fully described in cutaneous tumors and in Mohs micrographic surgery (MMS). OBJECTIVE: To evaluate MOC-31 labeling in BCC and other cutaneous tumors and to compare immunolabeling intensity of MOC-31 and Ber-EP4 in BCCs. MATERIALS AND METHODS: Nineteen permanently fixed and 29 frozen BCC specimens and 23 other cutaneous tumors were labeled with MOC-31; labeling intensity of tumors, epidermis, and adnexal structures were recorded. In a separate study, a blinded dermatopathologist compared labeling intensities of 8 BCC specimens, each labeled with MOC-31 and Ber-EP4.4. RESULTS: MOC-31 labeled all BCCs. Eccrine coils and follicular bulbs did label variably, although this did not detract utility of MOC-31. Five of thirteen cutaneous squamous cell carcinomas and one of two Merkel cell carcinomas demonstrated MOC-31 positivity. MOC-31 and Ber-EP4 labeled BCCs similarly. CONCLUSION: MOC-31, an antibody directed against Ep-CAM, is sensitive for BCCs in frozen specimens encountered in MMS and permanently fixed specimen. In addition, MOC-31 demonstrated comparable immunolabeling characteristics with Ber-EP4 for BCCs.